Comparison of ELISA with other serological tests in the diagnosis of ovine brucellosis - Öngör, H; Muz, A; Çetinkaya, B (Tubitak Scientific & Technological Research Council Turkey, 2001)
In this study, antibodies against Brucella melitensis in aborted sheep were investigated with enzyme-linked immunosorbent assay (ELISA), standard tube agglutination test (SAT), rose bengal plate test (RBPT), complement fixation test (CFT), 2-mercaptoethanol microagglutination test (2-ME-MAT) and dithiothreitol microagglutination test (DTT-MAT). The sensitivity and specificity of the tests were calculated by using CFT results as the gold standard. A Kappa value was used to measure the agreements between ELISA and the other tests. Sonicated antigen prepared from Brucella melitensis 16M strain, the peroxidase labelled anti-sheep IgG conjugate and orthophenylenediamine substrate were used in ELISA. A total of 500 blood samples collected from 36 sheep flocks in Elazig and environs were examined, One hundred and three (20.6%) samples in ELISA. 55 (11%) in RBPT, 84 (16.8%) in SAT, 89 (17.8%) in CFT, 79 (15.8%) in 2-ME-MAT and 81 (16.2%) in DTT MAT were found to be brucella-positive. In the comparison of these tests, a significant difference was detected between ELISA and RBPT results (p<0.001), whereas the differences between ELISA and other tests were not statistically significant (p>0.05), Excel lent agreement was detected between ELISA and CFT, DTT-MAT, 2-ME-MAT and SAT results. with kappa values of 88%, 84%. 83% and 85%, respectively. However, in the comparison of ELISA with RBPT, a kappa value of 64% (fair agreement) was obtained. in addition. the sensitivity and specificity of ELISA were determined to be 97% and 96%, respectively.
Atik Yapmiş Koyunlarda Brusellozis'in Teşhisinde ELISA ile Di?er Serolojik Testlerin Karşilaştirilmasi
Keywords: brucellosis; ELISA; serological tests; sheep; Brucella melitensis